2015
DOI: 10.3332/ecancer.2015.499
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy with propranolol and metronomic chemotherapy combination: sustained complete response of a relapsing metastatic angiosarcoma

Abstract: We report here a case of a 69-year-old woman with a relapsing metastatic angiosarcoma treated with a combination of metronomic chemotherapy and propranolol. The beta blockers were added since the tumour was positive for betaadrenergic receptor. A complete response was quickly obtained and lasted for 20 months.With this case, the combination of metronomic chemotherapy and propranolol in angiosarcoma warrants additional studies and illustrates the potential of metronomics to generate innovative yet inexpensive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…Banavali and colleagues reported on a case of relapsing metastatic angiosarcoma treated with a combination of metronomic oral low-dose chemotherapy (etoposide and cyclophosphamide), celecoxib and PRO (40 mg twice a day) [81]. The patient showed a complete response after two cycles of therapy.…”
Section: Human Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Banavali and colleagues reported on a case of relapsing metastatic angiosarcoma treated with a combination of metronomic oral low-dose chemotherapy (etoposide and cyclophosphamide), celecoxib and PRO (40 mg twice a day) [81]. The patient showed a complete response after two cycles of therapy.…”
Section: Human Datamentioning
confidence: 99%
“…Although no standard treatment exists, the majority of patients are treated with surgical resection, chemotherapy (doxorubicin or paclitaxel most commonly) and radiotherapy [182]. Given the high unmet needs in this disease, the case reports showing some benefit to patients using PRO in combination with other agents are noteworthy [44, 81, 82], along with responses to propranolol observed in other vascular tumours [41, 183184]. Clinical trials are urgently required to confirm the efficacy of these combinations with PRO.…”
Section: Our Takementioning
confidence: 99%
“…On the other side, in metronomics, the chemotherapeutic drugs are given in low doses or, at least, in doses lower than the maximum tolerated dose and repurposed drugs, as Cel, are administered with a metronomic schedule in the standard, nontoxic doses. In fact, it has already been demonstrated that metronomic chemotherapy is effective in different types of tumors and it is endowed of a low toxicity profile [26][27][28][29][30][31][32][33][34][35] b ringing about no deterioration of patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Banavali et al [28] reported a case of 69-year-old woman with relapsing metastatic skin angiosarcoma treated with a combination of metronomic chemotherapy and nonselective beta-blocker propranolol. The patient was treated with low doses of cyclophosphamide and etoposide along with nonsteroid anti-inflammatory drug (NSAID) celecoxib and propranolol.…”
Section: Discussionmentioning
confidence: 99%